Update on the Treatment of Metastatic Non-small Cell Lung Cancer (NSCLC) in New Era of Personalised Medicine - Barbara Melosky (Frontiers Research Topics, 2018)
Lung Cancer remains a major cause of death in of both women and men in our society. Lung cancer treatment paradigms have changed enormously as we've started to understand the genetic complexity and the multiple driver mutations influencing the disease. Therapeutics directed towards, or to inhibit signaling pathways has resulted in increased life spans for our patients. Over the last two decades, we have gone from simple chemotherapy used to treat all, to a personalized medicine approach for the majority. For non-small cell lung cancer patients without driver mutations, the world of immune oncology has arrived. These improved long-term outcomes mean that now our lung cancer patients can live with their cancers, but without progression. The aim of this book is to catalogue the current state of knowledge for the many facets of advanced lung cancer. It describes current treatment approaches for driver mutations, rare mutations, and rare thoracic malignancies such as neuroendocrine tumors. Most importantly, this book addresses the topics of palliative treatment and care which allow our patients to enjoy longer survival with the highest quality of life. We hope you enjoy this e-book. The future is brighter for lung cancer patients and as lung cancer specialists; we finally feel sense optimism about treatment options for our patients.